The Application of Consciousness Raising Activities in Senior High School English Textbooks - Burhansyah, Burhansyah; Samad, Iskandar Abdul; Mahmud, Masrizal (Journal of English Education and Teaching, 2025)
This research project explores the application of Consciousness Raising (henceforth C-R) activities in senior high school English textbooks, focusing on their presence and extent of implementation. C-R activities are instructional strategies that encourage learners to develop an explicit understanding of language structures rather than simply memorizing rules. This study seeks to determine whether such activities have been integrated into high school English textbooks and, if so, to what extent they are applied throughout the lessons.  The study employs a content analysis research method to systematically examine the inclusion of C-R activities within selected English textbooks used at the high school level. The analysis focuses specifically on the grammar lessons, identifying patterns in how C-R activities are incorporated into the instructional design. The findings indicate that all three textbooks examined consistently integrate C-R activities within their grammar lessons. Notably, these activities are most prominently featured in the Presentation stages of the lessons, where students are introduced to new grammatical structures. This suggests that the textbooks emphasize explicit awareness of grammar rules through structured exercises and discovery-based learning approaches.